In-Service Teachers’ Awareness and Professional Development in Egyptian Public Schools - Metawea, Hanan Mohamed (AUC Knowledge Fountain, 2025)
Neuroscience is an emergent field that focuses on studying brain structure and understanding its significance in the learning process. There has been a recent movement in how to bridge the gap between neuroscience concepts and education by incorporating neuroscience principles into the teaching process. However, there have been limited studies in Egypt on how educators understand and utilize neuroscience principles in the classroom. This qualitative exploratory case study examines Egyptian teachers’ understanding of neuroscience concepts and how they apply them in their teaching practices. This case study was carried out in two government schools, including interviews with 11 teachers representing a range of genders, academic specializations, and years of teaching experience. The findings revealed that the majority of teachers do not recognize the meaning of neuroscience; however, some teachers naturally adopt some brain-based teaching strategies as a result of their long teaching experiences. The participants reported that their teaching approaches are hampered by a variety of factors, including large class sizes, insufficient financing, a lack of opportunities for career development, and a lack of technological aids. In addition, even though most educators had limited specialized training on neuroscience, they expressed their desire and readiness to learn about this field so that they are able to incorporate its concepts into their teaching practices. As a result, the study recommends that additional studies be conducted into the establishment of neuroscience professional programs that boost teachers' awareness of how they can incorporate neuroscience concepts in the classroom. Toward that end, this study offers suggestions that can serve as the basis for establishing a successful neuroscience professional development plan for Egyptian teachers.